Video In Situ Snowfall Sensor (VISSS) data for Eriswil (2023-2024) - Maahn, Maximilian; Ettrichrätz, Veronika (PANGAEA, 2025)
The open source Video In Situ Snowfall Sensor (VISSS) is a novel instrument for the characterization of particle shape and size in snowfall. The VISSS consists of two cameras with LED backlights and telecentric lenses that allow accurate sizing and combine a large observation volume with relatively high resolution and a design that limits wind disturbance. Here you can find films and images of falling precipitation particles for the CLOUDLAB (Henneberger et al., 2023) and PolarCAP (Polarimetric Radar Signatures of Ice Formation Pathwaysfrom Controlled Aerosol Perturbations) project in Eriswil in winter 2023-2024. For further details on the VISSS instrument see Maahn et al. (2024).
Keywords: eriswil; In-situ experiment; precipitation; snowfall measurements